Does Time Since Injury and Time Spent in Physical Therapy Treatment Affect Outcomes for Concussion Patients?. (26th July 2019) - Moser, R; Zebrowski, C; Islam, S; Lemke, H; Schatz, P; James, M; Vidal, P
Abstract: Purpose: To evaluate the effects of: 1) time between injury and physical therapy treatment and 2) time spent in physical therapy, on concussion symptom resolution. Methods: Retrospective data was obtained for 202 patients who sustained a concussion and were referred for physical therapy. Subjects were assigned to groups based on type of injury (sport-related or not), time elapsed between concussion and therapy (0-14 days, 15–30, 31–60, 61–120, 121–365), and months spent in treatment (1 thru 4). Pre- and post- treatment scores were compared for the following measures: Sport Concussion Assessment Tool (SCAT), Convergence Insufficiency Symptom Survey (CISS), Dizziness Handicap Inventory (DHI), and Modified Clinical Test of Sensory Interaction on Balance (mCTSIB) using ANOVAs, with a Bonferroni-corrected p-value of p<.005. Results: There was no significant difference in outcomes for athletes vs. non-athletes on SCAT Symptom (p=.74) or Severity Score (p=.18), CISS (p=.52), DHI (p=.05), or mCTSIB (p=.10); in outcomes for time elapsed since injury on SCAT Symptom Score (p=.80), SCAT Symptom Severity Score (p=.97), CISS (p=.61), DHI (p=.65), mCTSIB (p=.13); or in outcomes for months in treatment on SCAT Symptom Score (p=.23), SCAT Symptom Severity Score (p=.04), CISS (p=.41), DHI (p=.37), mCTSIB (p=.50). Conclusion: Post-therapeutic improvements were noted for athletes receiving post-concussive physical therapy. Type of injury, time between injury and treatment, and time spent in treatment did not differentiate treatment outcomes for those receiving physical therapy post-concussion.